A Nitrate Reductase Inactivating Enzyme from the Maize Root - Wallace, W. (1973)
The nitrate reductase in the mature root extract of 3-day maize (Zea mays) seedlings was relatively labile in vitro. Insoluble polyvinylpyrrolidone used in the extraction medium produced only a slight increase in the stability of the enzyme. Mixing the mature root extract with that of the root tip promoted the inactivation of nitrate reductase in the latter. The inactivating factor in the mature root was separated from nitrate reductase by (NH(4))(2)SO(4) precipitation. Nitrate reductase was found in the 40% (NH(4))(2)SO(4) precipitate, while the inactivating factor was largely precipitated by 40 to 55% (NH(4))(2)SO(4). The latter fraction of the mature root inactivated the nitrate reductase isolated from the root tip, mature root, and scutellum. The inactivating factor, which has a Q(10) 15 to 25 C of 2.2, was heat labile, and hence has been designated as a nitrate reductase inactivating enzyme. The reduced flavin mononucleotide nitrate reductase was also inactivated, while an NADH cytochrome c reductase in nitrate-grown seedlings was inactivated but at a slower rate. The inactivating enzyme had no influence on the activity of nitrite reductase, glutamate dehydrogenase, xanthine oxidase, and isocitrate lyase. The activity of the nitrate reductase inactivating enzyme was not influenced by nitrate and was also found in the mature root of minus nitrate-grown seedlings.